LncRNA DCST1-AS1 Promotes Endometrial Cancer Progression by Modulating the MiR-665/HOXB5 and MiR-873-5p/CADM1 Pathways - Wang, Jie; Shi, Pingping; Teng, Huaixiang; Lu, Lixiang; Guo, Hailong; Wang, Xiuqin (Frontiers in Oncology, 2021)
Dysregulation of long non-coding RNA (LncRNA) is implicated in the initiation and progression of various tumors, including endometrial cancer (EC). However, the mechanism of lncRNAs in EC tumorigenesis and progression remains largely unexplored. In this work, we identified a novel lncRNA DCST1-AS1, which is highly upregulated and correlated with poor survival in HNSCC patients. Overexpression of DCST1-AS1 significantly enhanced EC cell proliferation, colony formation, migration and invasion in vitro and promoted tumor growth of EC in vivo. Mechanistically, DCST1-AS1 mediated EC progression by inducing the expression of HOXB5 and CADM1, via acting as a competing endogenous RNA for miR-665 and miR-873-5p, respectively. In addition, we found that the expression of miR-665 and miR-873-5p was significantly down-regulated, while HOXB5 and CADM1 expression levels were increased in EC tissues. Taken together, our findings support the important role of DCST1-AS1 in EC progression, and DCST1-AS1 may be used as a prognostic biomarker as well as a potential therapeutic target for EC.